Efektivitas Akupresur dan Minuman Jahe terhadap Pengurangan Intensitas Nyeri Haid/Dismenore Pada Remaja Putri - Indah Dewi Sari; Utary Dwi Listiarini (Universitas Batanghari Jambi, 2021)
Half of the women in Indonesia experience menstrual pain / dysmenorrhoea, 54.89%, experience various disorders including abdominal pain, cramps and back pain. The purpose of this study was to determine the effectiveness of acupressure, ginger drink and the difference in giving acupressure and ginger drink to reducing the intensity of menstrual pain / dysmenorrhea in young women at SMK Swasta PAB 5 Klambir Lima 2020. The design of this study used a quasi-experimental pre and post test with a sample of 30 students who were divided into two groups. Each group was given acupressure and ginger drink in the morning and evening during menstruation from day one to day two. Respondents were assessed for pain before and after the intervention was given. The results of the Shapiro-Wilk normality test contained Sig data (p <0.05). The Wilcoxon test has a p-value of 0.002 (p <0.05), which means that acupressure is effective in reducing the intensity of menstrual pain / dysmenorrhea, there is a p-value of 0.001 (p <0.05) which means that ginger is effective against reducing pain intensity. menstruation / dysmenorrhea, there is a p-value of 0.034 (p <0.05), which means that there is a difference in the effectiveness of acupressure and ginger drink in reducing the intensity of menstrual pain / dysmenorrhea. There is an effectiveness of giving acupressure, ginger drink, and there is a difference in giving acupressure and ginger drink on the intensity of menstrual pain / dysmenorrhea on young women. It is hoped that the school will provide ginger drinks and acupressure measures to young women who experience menstrual pain / dysmenorrhea so that they can participate in learning activities at school.